Effectiveness of the Control of Source of Venereal Diseases by Providing Transportation for Female Sex-Workers for Regular Check-up at STD&AIDS Center, Ratchaburi - Sangpudsa, Arun; Puengpean, Porntip; Sangkamanee, Thawin; Bunsirichai, Usa (Journal of Health Science of Thailand, 1995)
The authors had studied the control of sources of venereal disease infection by studying the outcomes of a measure operated in 1992 that provided transportation for female sex-workers to attend the STD&AIDS Center of Ratchaburi for regular health check-up, and compared with the outcomes for 1991 when no such service provided. It was found that sex workers had attended the Center more frequently in 1992 than in 1991 (97.0% vs 79.3% and 3 times a week vs 2 times a week). The incidence of sexually transmitted disease (STD) infections was much lower for the year 1992 (3.6% vs 7.3%). The cost of transportation service was much less than the total budget spent by individual transportation to the clinic. This measure should be considered a very effective intervention for provincial STD control programme.